(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The political crises in Rome had repercussions on all aspects of life. These repercussions included the various classes of society and all state institutions, judicial, political, administrative, and military. All of them were subject to change, including the Senate, through laws and legislation issued by the victorious parties. When Julius Caesar won the second civil war (49-44 BC), he initiated a set of social and governmental reforms, which included changing the Roman calendar from the lunar to the solar calendar. Caesar also carried out several other reforms that included the middle and low classes in Rome, including the distribution of subsidized grain by the state and the granting of Roman citizenship to many residents of remote areas. In addition to that, Caesar did land reform and support for veterans, and the number of senators was increased to make it an institution representing all parts of the republic. The devastating war that Rome was exposed to between Octavius (Augustus) on the one hand, and Mark Antony and Cleopatra on the other hand, undoubtedly had its impact and consequences on the political system and all aspects of life. This was especially clear after the victory of Octavius in the Battle of Actium (31 BC) and his uniqueness in the leadership of Rome after the change from the republican system to the imperial system.